PENGARUH PENGAWASAN, DISIPLIN KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN PT. SEMEN MERAH PUTIH KOTA BENGKULU - Elpi Widiya Ningsih; Eti Arini ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study aims 1). To determine the effect of supervision on employee performance at PT.Semen Merah Putih, Bengkulu City. 2). To determine the effect of work discipline on employee performance at PT.Semen Merah Putih, Bengkulu City. 3). To determine the influence of organizational culture on employee performance at PT.Semen Merah Putih, Bengkulu City. 4). To determine the effect of supervision, work discipline, and organizational culture on employee performance at PT. Semen Merah Putih, Bengkulu City. This type of research is a quantitative approach. With descriptive method. The population in this study were all employees at PT.Semen Merah Putih, Bengkulu City, amounting to 47 people. A good total sampling technique is used if the total population < 100. So the number of samples from this study is 47 customers. Based on the results of research on the influence of supervision, work discipline, and organizational culture on employee performance at PT. Red and White Cement Bengkulu City. The following conclusions can be drawn: 1). Supervision has a positive effect on the performance of employees of PT. Semen Merah Putih thus the higher the supervision it will improve the performance of employees at PT. Red and White Cement. 2). Work discipline has a positive effect on the performance of employees of PT. Semen Merah Putih thus the higher the work discipline it will improve the performance of employees at PT. Red and White Cement. 3). Organizational Culture has a positive effect on the performance of employees of PT. Semen Merah Putih thus the higher the Organizational Culture it will improve the performance of employees at PT. Red and White Cement. 4). Supervision, work discipline and Organizational Culture together show the effect on employee performance. Keywords: Supervision, work discipline, organizational culture and employee performance.